Body composition, dietary intake and physical activity of young survivors of childhood cancer. Issue 2 (April 2019) - Murphy-Alford, Alexia J.; White, Melinda; Lockwood, Liane; Hallahan, Andrew; Davies, Peter S.W.
Summary: Aim: To describe the body composition, dietary intake and physical activity and of paediatric, adolescent and young adult childhood cancer survivors (CCS) and examine the factors that impact body composition after treatment. Methods: This prospective cross-sectional study involved 74 subjects who were at least three years post treatment. Measurements included anthropometry, whole body potassium counting, air displacement plethysmography, and three day physical activity and diet diaries. Results: The CCS had significantly reduced body cell mass index Z-scores compared to controls (p = 0.0001), with 59% considered undernourished. The CCS had a significantly higher percent fat (p = 0.002) than the controls, with 27% classified as obese. The intake of 60% of CCS met estimated energy requirements, but the CCS consumed high amount of energy from fat and low amount of energy from carbohydrates. A high percentage of CCS did not meet their dietary requirements for calcium (61%), magnesium (46%), folate (38%) and iodine (38%). The CCS group had a light active lifestyle with 64% spending more than 2 h daily on screen time. Receiving a bone marrow transplant (r = −0.27; p = 0.02) and physical activity level (r = 0.49; p = 0.0001) were significantly correlated with body cell mass index. Conclusions: This study demonstrates that increased fat mass and decreased body cell mass is a concern for CCS and that CCS have poor health behaviours including light active lifestyles, excessive screentime, high fat intake, and poor intake of essential nutrients. This study has highlighted that CCS are at risk of both obesity and undernutrition and that increasing body cell mass as well as decreasing fat mass should be a focus of energy balance interventions in survivorship. There is a need for parents and children undergoing treatment for cancer to be educated about diet quality and importance of daily physical activity to ensure healthy habits are established and maintained into survivorship.